Cephalorhynchus heavisidii, Heaviside's Dolphin - Reeves, R. R. (2020)
This is a coastal, shallow-water dolphin seen mainly in waters less than 100 m deep (Best and Abernethy 1994). It is generally associated with the cold, northward-flowing Benguela Current. Rice and Saayman (1984) speculated that some subpopulations may be resident in particular areas year-round, although this was questioned by Best and Abernethy (1994). Satellite-linked tagging indicated that in summer female Heaviside?s dolphins occupied home ranges of up to 1,000-2,000 km² over periods of up to 54 days, with a strong onshore-offshore diurnal pattern of movement (Elwen et al., 2006). More than 85%of sightings were in water with surface temperatures of 9-15°C (Best and Abernethy 1994).